Computer modelling of pyrotechnic combustion - Taylor, Steven John (Rhodes University, Faculty of Science, Department of Chemistry, 1996)
One of the most important industrial uses of pyrotechnic compositions is as delay fuses in electric detonators. Many factors influence the rate of burning of such fuses. These include (a) the primary choice of chemical components, followed by (b) the physical properties of these components, particularly the particle-size and distribution of the fuel, (c) the composition of the system chosen and (d) the presence of additives and/or impurities. A full experimental study of the influences of even a few of these factors, while attempting to hold other potential variables constant, would be extremely time consuming and hence attention has been focused on the possibilities of modelling pyrotechnic combustion. Various approaches to the modelling of pyrotechnic combustion are discussed. These include:- (i) one-dimensional finite-difference models; (ii) two-dimensional finite-element models; (iii) particle-packing considerations; (iv) Monte Carlo models. Predicted behaviour is compared with extensive experimental information for the widely-used antimony/potassium permanganate pyrotechnic system, and the tungsten /potassium dichromate pyrotechnic system. The one-dimensional finite-difference model was investigated to give a simple means of investigating the effects of some parameters on the combustion of a pyrotechnic. The two-dimensional finite-difference model used similar inputs, but at the expense of considerably more computer power, gave more extensive information such as the shape of the burning front and the temperature gradients throughout the column and within the casing material. Both these models gave improved results when allowance was made for autocatalytic kinetics in place of the usual assumption of an "order-of-reaction", n â‰¤ 1. The particle-packing model investigated the qualitative relationship between the maximum burning rate of a pyrotechnic system and the maximum number of contact points (per 1.00 g composition) calculated for that system. Qualitative agreement was found for those systems which are presumed to burn mainly via solid-solid reactions. The Monte Carlo model investigated the effect of the random packing of fuel and oxidant particles on the variability of the burning rate of a pyrotechnic composition.
Keywords: Combustion -- Computer simulation